The Influence of Reading Skills on Students’ Popular Article Writing Performance in The Medical Laboratory Technology Program - Riyanti, Apriani; Ernawati, Lilis; Widodo, Nicolaus Sri; Achmadi, Achmadi; Aryani , Desi (Edukasi, 2026)
This quantitative correlational study examined the relationship between reading ability and popular article writing performance among Medical Laboratory Technology undergraduates at Universitas Binawan, Jakarta. Using purposive sampling, 120 students from semesters 4–6 (GPA ≥ 2.75) participated in the study. Data were collected through a 60-item reading comprehension test measuring literal (40%), inferential (35%), and evaluative (25%) comprehension levels (Cronbach's α = .87; M = 74.6, SD = 8.2) and an analytic writing rubric assessing content, organization, language use, and audience engagement (ICC = .89; M = 76.2, SD = 7.9; maximum score = 100). Simple linear regression analysis conducted via IBM SPSS 27.0 (α = .05) revealed that reading ability significantly predicted popular article writing quality (B = 0.68, t = 9.71, p < .001), explaining 46% of variance in writing performance (R² = .46, Adjusted R² = .45, F (1,118) = 94.25, p < .001). Students with higher reading proficiency demonstrated superior writing coherence, content accuracy, and audience adaptation. These cross-sectional findings, collected in May 2025, support the integration of reading-writing pedagogy in health sciences communication training within Indonesian higher education, particularly in programs aligned with the Merdeka Belajar Kampus Merdeka curriculum framework.